Recovery center selection for end-of-life automotive lithium-ion batteries using an integrated fuzzy WASPAS approach. (15th November 2022) - Pamucar, Dragan; Ebadi Torkayesh, Ali; Deveci, Muhammet; Simic, Vladimir
Highlights: Key question is how to identify the best location for an EoL ALiB recovery center. Integrated fuzzy MACBETH-D-WASPAS model is proposed to handle LiB management problems. Important influencing criteria for locating EoL ALiB recovery centers are provided. Arithmetic operations with Dombi norms in a fuzzy environment are greatly improved. Real-life case study of Istanbul is provided to illustrate the integrated fuzzy model. Abstract: With the emergence of battery-based electric vehicles, transportation systems gradually leave using fossil fuel-based combustion engines. Due to their reasonable performance, Lithium-ion batteries have become one of the major batteries used for electric vehicles. Although these batteries are being used in most companies, their high production cost, rare raw material, and short life cycle have raised important incentives for their recovery process. However, locating a recovery center for end-of-life Lithium-ion batteries is a multi-aspect decision making problem influenced by many criteria. For this purpose, a novel integrated decision-making model is developed based on Measuring Attractiveness by a Categorical Based Evaluation TecHnique (MACBETH) for calculating the criteria weights and Weight Aggregated Sum Product ASsessment (WASPAS) methods under the fuzzy environment with Dombi norms for evaluating the alternatives to address recovery center location selection problem considering technical as well as environmental, economic, and social aspects. To show the reliability and applicability of the developed method, a real-world case study in Istanbul is investigated. The developed method is used to evaluate six potential locations for the possible establishment of a recovery center. Results showed that Tuzla district is the most suitable location for opening a recovery center for end-of-life Lithium-ion batteries. Tuzla is in a very good position in terms of proximity to suppliers, transportation and location. To illustrate the robustness of the obtained results, extensive sensitivity analysis tests are performed.